2022
DOI: 10.1186/s12905-022-01604-5
|View full text |Cite
|
Sign up to set email alerts
|

Mothers with depressed mood: help-seeking from husbands and child-rearing behaviors

Abstract: Background Mothers with depressed mood tend not to seek help or support from others. Yet, there is no research providing a detailed examination of the processes that mothers with depressed mood undergo while seeking child-rearing support from their husbands. This study aimed to clarify the processes that mothers with depressed mood go through in seeking child-rearing support from their husbands and performing child-rearing duties. Methods The parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The narrow range of items within each support domain in the questionnaire may have also made the identification of more specific needs at each pint in the course of the distress more difficult. Other actions of emotional and tangible support not provided as questionnaire items, such as ‘respectfully discussing the mother's mood’, or ‘persisting in questioning if everything was OK’, may have elicited more information about when support was most helpful 31,55 . However, it may be impractical to address the breadth of issues involved in maternal distress in one study: a Delphi study aimed at preventing perinatal depression and anxiety resulted in 214 recommendations 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The narrow range of items within each support domain in the questionnaire may have also made the identification of more specific needs at each pint in the course of the distress more difficult. Other actions of emotional and tangible support not provided as questionnaire items, such as ‘respectfully discussing the mother's mood’, or ‘persisting in questioning if everything was OK’, may have elicited more information about when support was most helpful 31,55 . However, it may be impractical to address the breadth of issues involved in maternal distress in one study: a Delphi study aimed at preventing perinatal depression and anxiety resulted in 214 recommendations 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Other actions of emotional and tangible support not provided as questionnaire items, such as 'respectfully discussing the mother's mood', or 'persisting in questioning if everything was OK', may have elicited more information about when support was most helpful. 31,55 However, it may be impractical to address the breadth of issues involved in maternal distress in one study: a Delphi study aimed at preventing perinatal depression and anxiety resulted in 214 recommendations. 56 A more comprehensive approach utilising a larger group of mothers with experience of mental distress, and their partners, may facilitate an authentication of these support actions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number of mothers who experience loneliness during the child-rearing period has increased because the family structure in Japan has changed from extended family structures and relationships with neighbors in a community to a nuclear family. A sense of loneliness in child rearing was associated with increased anxiety (Katayama & Kitaoka, 2018). Anxiety and perceived lack of social support were risk factors for child abuse (Ninomiya et al, 2017).…”
mentioning
confidence: 99%
“…A study of Japanese women found that a lack of social support from a partner and socially strict and isolated families results in a 7-fold higher risk of PPD among women. On the contrary, the researchers concluded that women who have strong family and social ties with people with whom they can share their childcare challenges and difficulties have a lower risk of adverse mental health problems as the support they receive from loved ones represents a crucial protective factor against post-partum depression [35].…”
Section: Discussionmentioning
confidence: 99%